Investigation of microscale fracture mechanisms in glass–ceramics using peridynamics simulations - Prakash, Naveen; Deng, Binghui; Stewart, Ross J.; Smith, Charlene M.; Harris, Jason T. (Journal of the American Ceramic Society, 2022)
Glass–ceramics (GCs), obtained by controlled crystallization of a specially formulated precursor glass, are interesting materials that show great promise in obtaining superior properties compared to those of the precursor glass. Controlled crystallization enables creation of a microstructure with multiple phases which impacts macroscale properties in interesting ways. The present work develops microstructure‐scale computational models using the theory of peridynamics to investigate the increase in fracture toughness of GCs compared to traditional glass. Computational modeling is a promising tool to probe microstructural mechanics, but such studies in the literature are scarce. In this work, the theory of peridynamics, a non‐local theory of continuum mechanics, is applied to simulate crack propagation through microstructural realizations of a model lithium‐disilicate glass–ceramic. The crystalline and glassy phases within the microstructure are explicitly considered, with the size and shape of crystals inspired by experimental data. Multiple toughening mechanisms are revealed, which are functions of crystallinity and morphology, and the impact on fracture toughness is demonstrated. Crack path tortuosity is studied, and it is found that an optimum level of crack path tortuosity can be obtained in the range of 0.6–0.8 crystallinity. Numerical results are shown to agree well with previously published experimental and modeling results.